2018
DOI: 10.1080/0886022x.2018.1455592
|View full text |Cite
|
Sign up to set email alerts
|

Etiological analysis of graft dysfunction following living kidney transplantation: a report of 366 biopsies

Abstract: Aim: The aim of this study is to investigate the clinical features of graft dysfunction following living kidney transplantation and to assess its causes.Methods: We retrospectively analyzed a series of 366 living kidney transplantation indication biopsies with a clear etiology and diagnosis from July 2003 to June 2016 at our center. The classifications and diagnoses were performed based on clinical and pathological characteristics. All biopsies were evaluated according to the Banff 2007 schema.Results: Acute r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…The widespread use of effective immunosuppression has markedly reduced the risk of graft failure due to rejection in recent years [1] . Conversely, de novo or recurrent renal disease has become a major cause of graft dysfunction, which was confirmed in our previous study [2] , and it is the second leading cause of death-censored graft failure and the third leading cause of uncensored graft failure [3,4] .…”
Section: Introductionsupporting
confidence: 77%
“…The widespread use of effective immunosuppression has markedly reduced the risk of graft failure due to rejection in recent years [1] . Conversely, de novo or recurrent renal disease has become a major cause of graft dysfunction, which was confirmed in our previous study [2] , and it is the second leading cause of death-censored graft failure and the third leading cause of uncensored graft failure [3,4] .…”
Section: Introductionsupporting
confidence: 77%
“…We found that IgAN occurred frequently within 5 years postoperatively and then declined sharply in subsequent years, which was consistent with a previous report [18] . Few patients diagnosed with IgAN in renal allografts showed a remarkable increased sCr level when accepted biopsy [2] , as reported in previous study on IgAN in renal allografts, it had little impact on graft function in the early years after transplantation [19] , but Ortiz et al [20] found that the histopathological injury was not accompanied by abnormalities in the urinalysis in half of early recurrent IgAN patients. Therefore, the disease progression could be concealed, a protocol biopsy was recommended to prevent missed diagnoses, especially in clinically silent patients.…”
Section: Discussionmentioning
confidence: 73%
“…in total series, 27 cases without complete ultrasonic data 2. the baseline level at the time when patients had the lowest sCr level after transplantation, the same…”
mentioning
confidence: 58%
“…Predictive factors related to graft failure of IgAN in renal allografts calcineurin inhibitor; BKVAN, BK virus-associated nephropathy 1 the time from onset of initial symptoms to biopsy. 2 the eGFR at the time of the biopsy. The time from transplantation to IgAN in renal allografts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation